Synonymy of the yeast genera Moniliella and Trichosporonoides and proposal of Moniliella fonsecae sp nov and five new species combinations - Rosa, Carlos A.; Jindamorakot, Sasitorn; Limtong, Savitree; Nakase, Takashi; Lachance, Marc-Andre; Fidalgo-Jimenez, Abel; Daniel, Heide-Marie; Pagnocca, Fernando Carlos; Inacio, Joao; Morais, Paula B. (Soc General Microbiology, 2009)
Analyses of nucleotide sequences from the D1/D2 domains of the large-subunit rDNA and phenotypic characteristics showed that the genera Moniliella and Trichosporonoides are members of a single, monophyletic clade that would be best represented by a single anamorphic genus. on the basis of taxonomic priority, we propose the transfer of the five species of the genus Trichosporonoides to the genus Moniliella. The description of the genus Moniliella is emended and the following new combinations are proposed: Moniliella madida comb. nov., Moniliella megachiliensis comb. nov., Moniliella nigrescens comb. nov., Moniliella oedocephalis comb. nov. and Moniliella spathulata comb. nov. In addition, ten strains representing a novel yeast species belonging to the Moniliella clade were isolated from flowers in Thailand, Cuba and Brazil. Analysis of the internal transcribed spacer and D1/D2 large-subunit rDNA sequences indicated that the isolates represent a single species that was distinct from other species of the Moniliella clade. The name Moniliella fonsecae sp. nov. is proposed to accommodate these strains. The type strain is BCC 7726(T) (=CBS 10551(T)).